An assessment of Ebola-related stigma and its association with informal healthcare utilisation among Ebola survivors in Sierra Leone: a cross-sectional study - Peter Bai James; Jonathan Wardle; Amie Steel; Jon Adams (BMC, 2020)
Abstract Background We examined the magnitude and correlates of Ebola virus disease (EVD)-related stigma among EVD survivors in Sierra Leone since their return to their communities. In addition, we determined whether EVD-related stigma is a predictor of informal health care use among EVD survivors. Methods We conducted a cross-sectional study among 358 EVD survivors in five districts across all four geographic regions (Western Area, Northern Province, Eastern Province and Southern Province) of Sierra Leone. Ebola-related stigma was measured by adapting the validated HIV related stigma for people living with HIV/AIDS instrument. We also measured traditional and complementary medicine (T&CM) use (as a measure of informal healthcare use). Data were analysed using descriptive statistics and regression analysis. Results EVD survivors report higher levels of internalised stigma (0.92 ± 0.77) compared to total enacted stigma (0.71 ± 0.61). Social isolation (0.96 ± 0.88) was the highest reported enacted stigma subscale. Ebola survivors who identified as Christians [AOR = 2.51, 95%CI: 1.15-5.49, p = 0.021], who perceived their health to be fair/poor [AOR = 2.58, 95%CI: 1.39-4.77. p = 0.003] and who reside in the northern region of Sierra Leone [AOR = 2.80, 95%CI: 1.29-6.07, p = 0.009] were more likely to experience internalised stigma. Verbal abuse [AOR = 1.95, 95%CI: 1.09-3.49, p = 0.025] and healthcare neglect [AOR = 2.35, 95%CI: 1.37-4.02, p = 0.002] were independent predictors of T&CM use among EVD survivors. Conclusion Our findings suggest EVD-related stigma (internalised and enacted) is prevalent among EVD survivors since their return to their communities. Religiosity, perceived health status and region were identified as independent predictors of internalised stigma. Verbal abuse and healthcare neglect predict informal healthcare use. EVD survivor-centred and community-driven anti-stigma programs are needed to promote EVD survivors' recovery and community re-integration.